EFFECT OF HERDSMEN AND CROP FARMER CRISIS ON LIVELIHOOD OF FARMING HOUSEHOLDS IN KOGI STATE NIGERIA - Uyamasi, Irene M.; Oyeyemi, P. O.; Asiyanbi, O. A.; Duntoye, B. T.; Adewole, A. O.; Adara, C. T. (FUDMA JOURNAL OF SCIENCES, 2025)
The crisis between herdsmen and crop farmers have escalated in recent years from North Central region of Nigeria, threatening the livelihood of farming households which has unraveled the country’s social fabric, displaced some of the populace and resulted in a steady deterioration in the political and social activities of the country as a whole. This study examined the effect of herdsmen and crop farmer crisis on livelihood of the farming households in Kogi State, Nigeria. A simple random selection of 80 farmers from Oke-Dayo, Kabba Bunu rural locality of Kogi State was used for the study. A well-structured questionnaire was used for the data collection and descriptive Statistics were used to analyse the data generated from respondents. The study showed a good participation of female (male; 55%, female; 45%) in farming and revealed that the major causes of conflicts in the study area were uncontrolled grazing .Most of the crisis were yet unresolved in the study area. Meanwhile, farmland productivity was 87.5% before the herdsmen-crop farmers crisis resulting in increased crop production but after the clash, farmland became 60 % unproductive, in which 97.3% of crops were either destroyed or affected. Livestock and animal production were also affected.